Kontribusi Tafsir Anak bagi Pendidikan Islam Penyederhanaan Makna Ayat melalui Hermeneutika Sosial: Analisis Hermeneutika Sosial Ricoeur - Khoimatul Hasanah (Khulasah : Islamic Studies Journal, 2025)
This study examines two models of Qur’anic interpretation for children in Indonesia those authored by Abu Ady and Muhammad Muslih to analyze how the simplification of Qur’anic meanings is constructed through Paul Ricoeur’s social hermeneutics. The research is motivated by the growing need to present the Qur’an in a communicative, visually engaging, and developmentally appropriate manner for young readers. By analyzing the narrative structure, pedagogical strategies, and the configuration of meaning across Ricoeur’s three stages of mimesis, this study finds that the two works adopt distinct modes of simplification: Abu Ady employs an affective–narrative approach, whereas Muslih utilizes a more normative–literal explanatory style. These differences generate divergent forms of refiguration for child readers, particularly in terms of moral internalization, the formation of basic Qur’anic literacy, and the cultivation of early religious dispositions. The findings demonstrate that children’s tafsir functions not merely as a medium for simplifying Qur’anic texts but as an effective pedagogical mechanism for shaping socio-emotional character, nurturing spiritual awareness, and fostering moral sensitivity from an early age. Theoretically, this research extends the application of Ricoeur’s hermeneutics into the field of children’s Qur’anic interpretation an area previously underexplored by showing that the configurative processes within children’s tafsir constitute an active hermeneutical practice. Practically, the study implies the need for developing future children’s tafsir that integrates developmental psychology, adaptive visual design, and digital pedagogy to better meet the demands of contemporary Islamic education.